Оценка степени деформационной проработки колесных заготовок по изменению параметров дендритной структуры - Бабаченко, А.И.; Дёмина, Е.Г.; Кныш, А.В.; Хулин, А.Н.; Шпак, Е.А. (Вісник Українського матеріалознавчого товариства, 2016)
The effect of the incoming cast ingot parameters on deformation of a dendritic structure in elements of solid-rolled wheels has been investigated. It has been defined that the conditions of solidification of the incoming cast ingot have a major effect on the chemical heterogeneity due to dendritic segregation of elements such as silicon and manganese in the microstructure of the wheels tested samples after deformation. It has been shown that wheels manufactured from continuous cast billet characterized by a more dense dendritic structure, and as a result more uniform distribution of segregation areas.